KONSEP MANUSIA DALAM SISTEM PENDIDIKAN ISLAM - Amir, Dinasril (AT-TALIM, 2012)
Education concept closely relates to humansâ concept themselves. How humansâ concept will relate to their concept on education because the education itself is an effort to direct humansâ concept. Islamic concept on education is a holistic unit. This paper describes the humansâ concept that has dignity, well in nature, multidimentional, and multipotential. Thus, the Islamic education attempts to direct students become self-confidence, creative and innovative in developing their capabilities. New education system in Islam is determined by new concept on Islamic thinking.